2022
DOI: 10.1093/inthealth/ihac028
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm usually being my own doctor’: women's experiences of managing polycystic ovary syndrome in Canada

Abstract: Background Polycystic ovary syndrome (PCOS) is a complex, chronic condition characterized by anovulation, polycystic ovarian morphology and hyperandrogenism that requires lifelong management. To reduce the risk of comorbidity and to manage symptoms, lifestyle management and pharmaceuticals such as oral contraceptives are the most common forms of treatment and should be tailored to the individual patient. The literature to date has shown PCOS patients to experience widespread dissatisfaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
3
3
0
Order By: Relevance
“…In addition, respondents reported the need to advocate for themselves and to request referrals to specialist care. These findings are consistent with another Canadian study which reported a reliance on self-education and self-advocacy by respondents in their PCOS management [ 48 ]. A study by Hoyos et al found that almost all (98%) of survey respondents searched for information about PCOS on the internet [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, respondents reported the need to advocate for themselves and to request referrals to specialist care. These findings are consistent with another Canadian study which reported a reliance on self-education and self-advocacy by respondents in their PCOS management [ 48 ]. A study by Hoyos et al found that almost all (98%) of survey respondents searched for information about PCOS on the internet [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The delay in diagnosis may be attributable to insufficient medical training of physicians in women’s health issues related to menstruation and PCOS specifically, and a lack of referral to endocrine and women’s health specialists [ 33 , 47 ]. Our data is consistent with other reports of a protracted diagnosis of PCOS taking greater than two years, and associated with multiple visits to health professionals and examination by three or more physicians before a diagnosis [ 2 , 30 , 48 ]. It is not clear whether these diagnostic delays are associated with a lack of physician education and training about PCOS and diagnostic criteria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…27 Furthermore, a lack of empathy and weight bias from health professionals seemed to enhance the feeling of stigmatization of patients in this study. 28 A recent study out of India looking at PCOS treatment seeking pathways in newly diagnosed patients observed that recurrent lack of clear treatment explanations led to 51% of patients consulting two to three healthcare agencies for treatment recommendations. 29 Even though similar treatment plans were provided at each consultation, a lack of insight into the PCOSspecific medical decision-making left patients unable to accept treatment recommendations.…”
Section: Current Communication Needs In Individuals With Pcosmentioning
confidence: 99%
“…A total of 13 studies 23,24,[29][30][31][32][33][34][35][36][37][38][39] were included in this systematic review, of which 11 were qualitative studies and two were mixed studies that reported the results of qualitative studies in detail. Of the 13 studies, four were from Australia, three were from the United States, two were from India, and the remaining four were from New England, the United Kingdom, Canada, and Iran.…”
Section: Study Characteristicsmentioning
confidence: 99%